Risk factors for potential drug-drug interactions in a general neurology ward - Kostić Marina J.; Živković-Zarić Radica S.; Janković Slobodan M. (Vojnosanitetski Pregled)
Bacground/Aim. Treatment of neurological diseases usually requires polypharmacy, and it is crucial to detect potential drug-drug interactions (DDIs) and recognize risk factors on time, as consequences of DDIs could be serious. The aim of the study was to analyze risk factors for the occurrence and the number of potential DDIs among patients in a general neurological ward. Methods. This study was conducted with 144 inpatients in a general-care neurological department of a tertiary care hospital. The effects of risk factors for potential DDIs were evaluated by multiple linear regression. The study had retrospective cohort de-sign. Frequencies of various types of potential DDIs (according to severity) were discovered by Medscape, Epocrates and Micromedex online interaction checkers. Results. The number of prescribed drugs, age of a patient, value of the Charlson comorbidity index and prescription of an antidepressant increase risk of potential DDIs in a general neurology ward. On the other hand, being paralyzed, number of prescribers for a single patient, being bedridden for at least one day of hospitalization decreased the number of potential DDIs per patient. Number of prescribed drugs per patient [odds ratio (OR) = 1.466 ± 0.250; p = 0.000) and age (OR = 1.027 ± 0.026; p = 0.041)] increased, and number of prescribers per patient (OR = 0.056 ± 0.028; p = 0.016), especially if the patients were paralyzed (OR = 0.214 ± 0.294; p = 0.007), decreased the risk of contraindicated, serious, “use alternative” or major potential DDIs. Antidepressants increased the risk of absolute number of all monitor/modify potential DDIs (OR = 1.257 ± 0.726; p = 0.035). Conclusion. Frequency of potential DDIs among neurological patients is considerable and influenced to the largest extent by advanced age, comorbidities, total number of pre-scribed drugs per patient and concomitant use of antidepressants.